A sociological study of the significance of identity and ageing in a North Sami community. Issue 1 (31st December 2023) - Gjernes, Trude; Anderssen, Jorid
ABSTRACT: This article explored experiences of ageing from interviews with a sample drawn from a population living in a North Sami community. Our focus is on older adult's involvement in activities that emphasise and maintain them as participants in specific kinds of activities that require knowledge, skills and mentorship, and to what degree it provides them with social capital and ethnic identity. We present data from in-depth interviews with female and male inhabitants ranging from 29 to 75 years of age. Thematic analysis of the data indicates that social capital and identity are particularly apparent within three contexts: 1. family and social relationships, 2. reindeer herding and other traditional labour and 3. Sami language. We conclude that older people hold vital positions in the local community regarding these three contexts. They transfer and reproduce cultural competence, and they manifest their roles and positions as active and valuable cultural members and practical contributors to the community. Their cultural involvement is not performed for their own advantage but is a regular part of their everyday lives, benefiting their special position within this sociocultural context and creating social capital.